Only the brave ebook A novel. - Steel, Danielle (2024)
NEW YORK TIMES BESTSELLER • From #1 New York Times bestselling author Danielle Steel comes a powerful, sweeping historical novel about a courageous woman in World War II Germany. Sophia Alexander, the beautiful daughter of a famous surgeon in Berlin, has had to grow up faster than most young women. When her mother falls ill, Sophia must take charge of her younger sister, Theresa, and look after her father and the household, while also volunteering at his hospital after school. Meanwhile, Hitler’s rise to power and the violence in her very own town have Sophia concerned, but only her mother is willing to share her fears openly. After tragedy strikes and her mother dies, Sophia becomes increasingly involved in the resistance, attending meetings of dissidents and helping however she can. Circumstances become increasingly dangerous and personal when Sophia assists her sister’s daring escape from Germany, as Theresa flees with her young husband and his family. Her father also begins to resist the regime, secretly healing those hiding from persecution, only to have his hospital burned to the ground. When he is arrested and sent to a concentration camp, Sophia is truly on her own, but more determined than ever to help. While working as a nurse with the convent nuns, the Sisters of Mercy, Sophia continues her harrowing efforts to transport Jewish children to safety and finds herself under surveillance. As the political tensions rise and the brutal oppression continues, Sophia is undeterred, risking it all, even her own freedom, as she rises to the challenge of helping those in need—no matter the cost. In Only the Brave , Danielle Steel vividly captures the devastating effects of war alongside beautiful moments of compassion and courage.